A Research on Working Capital Management Efficiency and Performance in Indian Industries: The Impact of Working Capital Management on Profitability in Indian Industries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Efficient management of working capital is a fundamental part of the overall corporate strategy in creating the shareholders’ value. Today the management of Working Capital is one of the most important and challenging aspect of the overall financial management. Optimization of working capital balance means minimizing the working capital requirements and realizing maximum possible revenues. Efficient WCM increases firms’ free cash flow, which in turn increases the firms’ growth opportunities and return to shareholders. Even though firms traditionally are focused on long term capital budgeting and capital structure, the recent trend is that many companies across different industries focus on WCM efficiency. Financing decision of an entity bears relation with working capital management. It is a part of short term financing. The study of corporate finance is also linked with Working capital management. Thus, this study sought to examine the effect of working capital management on profitability of select companies listed in BSE The study used a sample of 53 companies. The study used secondary data for a period of 5 years from 2011 – 2015. The data have been analysed using the Pearson correlation and the multivariate regression analysis. The study has revealed that the all components of working capital namely Receivable days( RD), Payable days(PD), Inventory holding periods ( ID), Current ratio ( CR) and Quick ratio ( QR) have strong impact on profitability. Cash conversion cycle (CCC) is negatively related with the profitability, Firm size is also linked with working capital. If firm size increases, the need of working capital will be more. It has been found that the firm size has also significant impact on EBIT but insignificant impact on ROA and ROE.